2019
DOI: 10.1262/jrd.2019-026
|View full text |Cite
|
Sign up to set email alerts
|

The transfer of parthenogenetic embryos following artificial insemination in cows can enhance pregnancy recognition via the secretion of interferon tau

Abstract: Repeat breeding is a reproductive disorder in cattle. Embryo transfer following artificial insemination (AI) improves pregnancy rate by replenishing interferon tau (IFNT), but it results in a notably higher rate of twin occurrence. This study hypothesized that parthenogenetic (PA) embryo transfer following AI (AI + PA) could improve the conception rate because that PA embryo become as a supplemental source of IFNT without twins. PA embryos showed higher IFNT mRNA expression than in vitro fertilization (IVF) em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Repeat breeding Holstein cows were defined by characteristics [ 1 , 17 ] that include detectable estrous behavior with occasional abnormal estrous cycles, healthy uterus and ovaries as determined by transrectal palpation, and the inability to conceive after four or more AIs following normal estrous behavior. After selection of 5 repeat breeder cows, the estrous cycle was synchronized using the method used for healthy cows; then blood and uterine fluid was collected from these repeat breeder cows on day 7 of the estrous cycle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeat breeding Holstein cows were defined by characteristics [ 1 , 17 ] that include detectable estrous behavior with occasional abnormal estrous cycles, healthy uterus and ovaries as determined by transrectal palpation, and the inability to conceive after four or more AIs following normal estrous behavior. After selection of 5 repeat breeder cows, the estrous cycle was synchronized using the method used for healthy cows; then blood and uterine fluid was collected from these repeat breeder cows on day 7 of the estrous cycle.…”
Section: Methodsmentioning
confidence: 99%
“…After selection of 5 repeat breeder cows, the estrous cycle was synchronized using the method used for healthy cows; then blood and uterine fluid was collected from these repeat breeder cows on day 7 of the estrous cycle. In our previous investigations, we transferred in vitro fertilized embryo or parthenogenetic embryo on day 7 after estrus following artificial insemination in repeat breeder cows to improve pregnancy recognition [ 17 , 18 ]. Therefore, in the present study, we collected samples to investigate the condition of blood and uterine fluid in the same timing with previous study.…”
Section: Methodsmentioning
confidence: 99%
“…Although the causes of repeat breeder cows were multifactorial and various treatment options for repeat breeder cows were investigated, parthenogenetic embryo transfer following AI increases the conception rate in repeat breeder lactating dairy cows in a recent study [ 32 ]. Parthenogenetic embryos show higher interferon-tau mRNA expression and induce higher interferon-tau stimulated gene mRNA expression in the white blood cells of cows that was transferred parthenogenetic embryo in the uterus [ 32 ]. From these results, one of the causes of infertility in the repeat breeder cows might have been a shortage of interferon-tau secretion from the embryo.…”
Section: Discussionmentioning
confidence: 99%
“…RBCs in the university farm were defined by following ( Dochi et al, 2008 ; Funeshima et al, 2019 ): RBCs showed normal estrous behavior, normal uterus and ovaries as determined by observation using ultrasound diagnostic, and the inability to conceive after four or more AIs following normal estrous behavior ( n = 5). Then, the estrous cycle was synchronized using the above method used for normal fertile cows.…”
Section: Methodsmentioning
confidence: 99%